A Review the Important of Green Human Resource Management Practices toward Employee Green Behaviour in Organization - Luh Titisari Dewi Adriana; Keke Tamara Fahira; Maulida Nailissa’adah; Hikmah El Maula (AIBPM Publisher, 2020)
Nowadays, the concerns of environment are becoming a very important global issue, including for organizations. The existence of an organization in the long term depends on the application of its environmental policies. Responding to a greater Environmental Awareness, organizations are becoming more concerned about managing green human resources (GHRM). Attention to employee green behavior appear from the employee’s necessities to use resources wisely and responsibly. Although the literature on GHRM gets a great attention and discussion among industry practitioner, however research that showed GHRM’s practice and its contribution to employee green behavior in organization is limited and requires more review in the academic literature. The aims of this research are (1) reviewed the literature on the relationship between GHRM practices and employee green behavior in organization; (2) explore the definitions provided by researchers regarding the term